Kontribusi Komunikasi Interpersonal dan Self Confidence Mahasiswa terhadap Pengetahuan Mata Kuliah Communication And IPE di Poltekkes Kemenkes Surakarta - Syarifah, Syarifah; Yonaevy, Umy (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Knowledge competence in the Communication and Interprofessional Education course plays an essential role in preparing students for collaborative professional practice. Several factors are believed to influence this competence, particularly students’ interpersonal communication skills and their confidence during the learning process. Understanding these factors is crucial to improving interprofessional education quality in health institutions. Objectives: This study aimed to analyze the contribution of interpersonal communication and confidence to the knowledge competence of students in the Communication and Interprofessional Education course at Poltekkes Kemenkes Surakarta. Methods: This research employed an ex post facto design involving two hundred and ten students enrolled in the course. Interpersonal communication and confidence data were collected through questionnaires, while knowledge competence data were obtained from academic records. Linear regression analysis was used to determine the contribution of each variable. Results: The results show that interpersonal communication contributes 54,1% percent to knowledge competence, while confidence contributes forty-seven point three percent. The combined contribution of both variables reaches 58,5%, indicating a strong influence on students’ academic understanding in the course. Conclusion: Interpersonal communication and confidence significantly contribute to students’ knowledge competence in the Communication and Interprofessional Education course. Strengthening these factors is necessary to enhance the effectiveness of interprofessional education. Keywords: Interpersonal communication, Confidence, Knowledge competence, Interprofessional education